2003
DOI: 10.1093/cercor/13.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Cues on Macaque Inferior Temporal Cortical Responses

Abstract: Humans are able to recognize objects when surface details, such as colour, texture and luminance gradients, are not available. By systematically eliminating colour, texture, shading, contrast and inner contours from given objects, we tested whether certain shape-selective inferior temporal cortex (IT) neurons of awake rhesus monkeys remain selective for these objects as the surface information is reduced. In psychophysical experiments, we established that the rhesus monkey can identify the shape of a coloured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
6
28
0
Order By: Relevance
“…However, because characterizations of tuning have typically been performed along the dimension of interest (shape or color) while holding the other (color or shape) constant, past V4 results do not reveal whether selectivity for form and color interact at the single-neuron level, i.e., whether shape preferences are the same regardless of the color of the stimulus. Our findings of consistency in shape selectivity across colors in V4 are in keeping with previous results from IT cortex which suggest that selectivities for color and shape are largely independent of each other (Komatsu and Ideura 1993) and that shape preferences are consistent across contrast reversals (Kovacs et al 2003). One previous study (McMahon and Olson 2009) demonstrated that influences of color and shape sum additively for most neurons in IT cortex and that nonlinear interactions between these stimulus attributes were rare.…”
Section: Discussionsupporting
confidence: 91%
“…However, because characterizations of tuning have typically been performed along the dimension of interest (shape or color) while holding the other (color or shape) constant, past V4 results do not reveal whether selectivity for form and color interact at the single-neuron level, i.e., whether shape preferences are the same regardless of the color of the stimulus. Our findings of consistency in shape selectivity across colors in V4 are in keeping with previous results from IT cortex which suggest that selectivities for color and shape are largely independent of each other (Komatsu and Ideura 1993) and that shape preferences are consistent across contrast reversals (Kovacs et al 2003). One previous study (McMahon and Olson 2009) demonstrated that influences of color and shape sum additively for most neurons in IT cortex and that nonlinear interactions between these stimulus attributes were rare.…”
Section: Discussionsupporting
confidence: 91%
“…While this is certainly a key property of IT neurons, one should keep in mind (Fig. 9) that 1) we are still uncertain about exactly what it is that the IT neurons represent, since living organisms are far more important to the monkey than most man-made objects; 2) the representation of objects, including animate entities, may not be the only goal of IT processing, and representation of scenes is perhaps just as important; and 3) the processing of two-dimensional shape is important for building these "object" and scene representations but processing of other aspects such as three-dimensional shape and material properties, including volumetric texture and color, are also important (1,134,135,139,251,301). Thus IT neurons might be selective for complex image attributes other than two-dimensional shape, and two-dimensional shape itself may be integrated into even higher attributes.…”
Section: Two-dimensional Shape Processing In Infero-temporal Cortexmentioning
confidence: 99%
“…Indeed, several studies in macaques and pigeons have shown that these animals failed to demonstrate a positive transfer from an original object to its line drawing (e.g., Tolan et al, 1981; Young et al, 2001; Peissig, Young, Wasserman, & Biederman, 2005). Thus far, there is only limited evidence for successful transfer to line drawings in non-human primates, and this concerned a very small number of subjects (e.g., Kovacs et al, 2003), few highly simple stimuli (e.g., Zimmermann & Hochberg, 1970), or language-trained chimpanzees (e.g., Hayes & Hayes, 1953; Itakura, 1994). We believe that our experiment overcomes the limitations of previous experiments by testing five macaques in the recognition of eight different rigorously designed objects, and thus provides two major conclusions.…”
Section: Discussionmentioning
confidence: 99%